Haunting Apartheids : Melancholy Reminiscences In J.M. Coetzee's Summertime. Issue 1 (2nd January 2016) - Birks, Cécile
ABSTRACT: J.M.Coetzee's Summertime examines the intricacies of the personal itinerary of a white male writer in the making, a Mr John Coetzee, and the maturation of a literary oeuvre at the height of apartheid. This introspective narrative, alongside the highly complex self-conscious and self-ironic strategies which make Coetzee's partly autobiographical text a unique literary object, is a poignant revisitation of the haunting 1970's in South Africa. Summertime discusses the complex political and ideological framework that shaped, stifled and fractured the society and culture his protagonist had grown up in and away from but also to some extent the geographical, sociological, racial and linguistic transformations that had started to take place and against the apartheid regulations and oppression. Thus it both chronicles and deconstructs several strata of apartheids, as well as their lethal set-up that eventually led to the final disintegration of the regime.